Seasonal and individual predictors of diet in a free‐ranging population of mandrills. (3rd July 2017) - Nsi Akoue, Gontran; Mbading‐Mbading, Wilfried; Willaume, Eric; Souza, Alain; Mbatchi, Bertrand; Charpentier, Marie J. E.
Abstract: Deciphering the dietary habits of a species is central to understanding its ecology, resource requirements, and the evolution of its life history traits. Detailed information on how primates use their environment to address their nutritional needs is available for many primate species. Such basic, but necessary data are, however, fragmented for secretive primates, especially regarding direct behavioral observations of individuals. In this study, we evaluated the impact of seasonality and demographic characteristics on diet and feeding habits in the only free‐ranging population of habituated mandrills ( Mandrillus sphinx ), a forest‐dwelling species inhabiting the dense humid forests of Central Africa. We collected fine‐grained quantitative data on feeding behavior of 57 individually‐recognized animals of both sexes and different age classes during a 17‐month period. We identified most consumed plant species and determined their abundance in the habitat of the studied mandrills. We showed that diet in this species was extremely diverse and included approximately 150 different plant species, but also mushrooms, invertebrates, and vertebrates. This omnivorous and highly diverse diet presented, however, a clear frugivorous tendency. While we identified three food items largely consumed throughout the year, we also found a strong seasonal signature on diet that was partly, but not only, related to food availability. Age and sex also influenced feeding habits with some feeding specializations according to the individual categories considered and their associated nutritional needs. Our quantitative data provide a basis for future studies examining the nutritional and mineral content of food items, which will further elucidate important aspects of the ecology of this little studied forest primate.